2018
DOI: 10.1038/s41598-018-32305-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electromagnetic Stimulation of Amaranth Seeds of Different Initial Moisture on the Germination Parameters and Photosynthetic Pigments Content

Abstract: The influence of stimulation with He-Ne laser light, alternating magnetic field and the combination of these factors on germination parameters of amaranth seeds and on the chlorophyll and carotenoid content in seedlings was investigated. During the stimulation the amaranth seeds had a different initial moisture content. From the germination characteristics of the seeds as the function of humidity, three maxima and one minimum value of the germination parameters (the relative germination capacity NK REL, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
0
21
0
2
Order By: Relevance
“…There is a small amount of work devoted to the investigation of ELFMFs on photosynthesis and relating processes (see reviews [ 27 , 28 , 29 , 30 ]). Moreover, only few works show the influence of these MFs on photosynthesis in plant seedlings [ 36 , 39 ]; other works investigate the influence on photosynthetic parameters in plants after seed treatments by ELFMFs [ 35 , 37 , 38 ]. Our current work, which is devoted to the analysis of the influence of ELFMFs with 7.8, 14.3, and 20.8 Hz frequencies (the first, second and third Schumann resonance frequencies) on parameters of photosynthetic light reactions, shows the following points:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a small amount of work devoted to the investigation of ELFMFs on photosynthesis and relating processes (see reviews [ 27 , 28 , 29 , 30 ]). Moreover, only few works show the influence of these MFs on photosynthesis in plant seedlings [ 36 , 39 ]; other works investigate the influence on photosynthetic parameters in plants after seed treatments by ELFMFs [ 35 , 37 , 38 ]. Our current work, which is devoted to the analysis of the influence of ELFMFs with 7.8, 14.3, and 20.8 Hz frequencies (the first, second and third Schumann resonance frequencies) on parameters of photosynthetic light reactions, shows the following points:…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of works (see reviews [ 27 , 28 , 29 , 30 ]), which show the influence of ELFMFs on photosynthesis and related processes. In particular, treatment by ELFMF can change the content of chlorophylls and carotenoids [ 35 , 36 , 37 , 38 ], stimulate gene expression of ribulose 1,5-bisphosphate carboxylase/oxygenase small subunit [ 36 ], influence photosynthetic CO 2 assimilation and transpiration [ 36 , 38 , 39 ]. However, there are only few studies, which are devoted to investigation of the influence of ELFMFs on plant seedlings [ 36 , 39 ]; other works are devoted to the influence of these magnetic fields on seeds [ 35 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid qualitative adjustment in leaf photosynthetic apparatus and photosynthetic capacity can occur in response to short alterations in light availability 50 . As a major change, sun-exposed plants tends to increase the Chl a / b ratio 51 . This general finding was also confirmed in the current study, as a higher photosynthetic levels and Chl a / b ratio were observed in DP leaves with relatively higher irradiance (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…414 Kornarzynski and his colleagues reported growth promotion of this plant by electromagnetic stimulation to enhance the production of pigments (chlorophylls and carotenoids) in leaves. 415 Hlinkova and her colleagues grew this plant for two consecutive years and discovered high content of fatty acids (seeds) with notable unsaturation index (UI). 416 As we mentioned earlier, Amaranthus palmeri also has not been investigated much.…”
Section: Chemical Compositionmentioning
confidence: 99%